Determinants for development of cluster initiatives in Poland and Ukraine - Ewa Kochanska; Mykola Kyzym; Viktoria Khaustova; Andrzej R. Klimek; Iwona Adamkiewicz (ACTA INNOVATIONS, 2016)
The article analyses the problems of cluster development in Poland and Ukraine in order to identify directions for possible cooperation between the countries. Specificity and priorities of the national policies of clusters development, regional systems of support and examples of good practices of clustering in the both countries were considered. The comparative analyses of prospects for clusters development in Poland and Ukraine were conducted, the basic determinants influencing the cluster development were identified and evaluated. There were recognized the areas and direction of Polish-Ukrainian clusters cooperation including: the opportunities to projects conducting within the European Funds, the possibilities of bilateral cooperation of cluster members with the support of cluster coordinators, the feasibility of joint Polish-Ukrainian projects run in third countries markets.